A Literary Perspective on Schenker's Jewishness. (20th July 2015) - REITER, ANDREA
ABSTRACT Heinrich Schenker was a keen observer of and participant in the cultural life of his time. In his diary he diligently recorded his impressions about a wide variety of cultural events, and recent scholarship has recognised the impact of his cultural environment on his theoretical work. This essay explores Schenker's views about his Jewishness as they become apparent in his response to several literary texts. Following an examination of his comments on Jews and Jewishness, I discuss three entries on literary works with a Jewish subject: Karl Kraus's poem 'Gebet an die Sonne von Gibeon', John Galsworthy's play Loyalties and Sholem Asch's story 'Der reiche Herr Salomon'. Schenker's 'literary criticism' exemplifies three principal Jewish concerns in his thinking: the biblical foundation of Judaism, the relationship between Jews and the people among whom they live and the Jew as an exemplary human being. Critiquing these texts allowed Schenker to highlight the characteristics of the Jews as a people and as individuals, Jewish monotheism, the Jews' predisposition to studying and thinking and their philanthropic attitude. Most important, the Jews who appear in these texts reinforced his own positioning as a Jew and a professional in a non‐Jewish environment.